Thermal Balance of the Body and Methods of Heat Exchange - Utkurxodjayevna , Kattaxodjayeva Dinara; o’g’li , Mirabzalzoda Muxamadvorisxon Mirsulton; Shuxratbekovich , Zaxidov Muhammad (American Journal of Bioscience and Clinical Integrity, 2025)
It is shown that heat exchange occurs on the body’s surface and involves four main modes: conduction, convection, radiation, and evaporation. It is also shown that heat transfer occurs only through the evaporation of fluid from the body’s surface, as a person evaporates 0.3-0.4 liters of fluid from the mucous membranes of the respiratory tract per day. Entropy is a physical quantity characterizing the value of a given system per unit temperature. States characterized by high order have a relatively low probability. Low-order states have a high probability of existence. Conversely, the degree of order in a system is characterized by its entropy.